The Fall and Recovery of the Cuban Economy in the 1990's : Mirage or Reality? - Hernandez-Cata, Ernesto (Washington, D.C. : International Monetary Fund, 2001)
The collapse of the Cuban economy following the cessation of Soviet assistance gave way to a strong recovery in 1994-96. There are three possible explanations for this recovery: (i) that it never took place; (ii) that it reflected a surge in productivity resulting from stabilization and liberalization in 1993-94; or (iii) that it resulted from a favorable aggregate demand shock. The second explanation-the most persuasive-suggests that a strong and durable expansion will probably not be achieved on the basis of present policies, but that the benefits of a full liberalization of the economy are likely to be considerable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet